Nationwide population‐based study of trends and regional variation in breast‐conserving treatment for breast cancer. Issue 13 (9th August 2018) - van Maaren, M. C.; Strobbe, L. J. A.; Koppert, L. B.; Poortmans, P. M. P.; Siesling, S.
Abstract : Background: Landmark trials have shown breast‐conserving surgery (BCS) combined with radiotherapy to be as safe as mastectomy in breast cancer treatment. This population‐based study aimed to evaluate trends in BCS from 1989 to 2015 in nine geographical regions in the Netherlands. Methods: All women diagnosed between 1989 and 2015 with primary T1–2 N0–1 breast cancer, treated with BCS or mastectomy, were identified from the Netherlands Cancer Registry. Crude and case mix‐adjusted rates of BCS were evaluated and compared between nine Dutch regions for two time intervals: 1989–2002 and 2003–2015. The annual percentage change in BCS per region over time was assessed by means of Joinpoint regression analyses. Explanatory variables associated with the choice of initial surgery were evaluated using multivariable logistic regression. Results: A total of 202 934 patients were included, 82 200 treated in 1989–2002 and 120 734 in 2003–2015. During 1989–2002, the mean rate of BCS was 50·6 per cent, varying significantly from 39·0 to 71·7 per cent between the nine regions. For most regions, a marked rise in BCS was observed between 2002 and 2003. During 2003–2015, the mean rate of BCS increased to 67·4 per cent, but still varied significantly between regions from 58·5 to 75·5 per cent. A significant variation remained after case‐mix correction. Conclusion: This large nationwide study showed that the use of BCS increased from 1989 to 2015 in the Netherlands. After adjustment for explanatory variables, a large variation still existed between the nine regions. This regional variation underlines the need for implementation of a uniform treatment and decision‐making strategy. Abstract : Regional differences remain